Migration, Contemporary Literature, Eastern Europe: In Search of a Term (KULT_online, 2022)
This interdisciplinary volume is devoted to the literature of authors of Central Eastern, Southeastern, and Eastern European origin writing in German. The editors and most of the contributors address the problem of categorizing of this literary phenomena, making an important contribution to the field of research. The volume explores theoretical and historical aspects, as well as individual analyses from literary, linguistic, and translation studies perspectives.